The Serbian Orthodox Church in the 90s - Radić, Radmila (Poznańskie Studia Slawistyczne, 2016)
This paper is based on the earlier works of the author (incurred mainly on the analysis of the press of state and Church provenance), surveys of sociologists of religion, and findings of other researchers dealing with the issues of the Serbian Orthodox Church. Several characteristic points could be drawn that marked the history of the Church in the late 80s and throughout the 90s: the Church’s return from the margins and its more significant presence in society; accelerated process of desecularization; complicated relationship to authorities, ranged from the first closeness to the complete break and disappointment over unfulfilled expectations of the Church; refusal to admit the divisions and the creation of new states formed into the wars on 90s, which for the Church constituted acts of violent secession to detriment of the Serbian people; negative attitudes to the West, ecumenism, Vatican and interfaith dialogue; efforts to resolve the issue of schism within the Church; and growing internal contradictions in the episcopate. Entering unprepared for transition processes that led from one political system to another, followed by the wars and the collapse of the state, and movements into the Church, the Serbian Orthodox Church has tried to oscillate between maintenance of the traditional role of the national Church, and a gradual adjustment to the changes, in aim to avoid major consequences for ecclesiastical organization.